Composição fitoquímica, atividade antioxidante e validação de método UPLC-DAD para determinação flavonóides da Thuya occcidentalis (Cupressaceae) - Santana, Danielle Bezerra de (2019)
Thuja occidentalis is a plant from Cupressaceae family with a long history of use on traditional medicine being used to treat various diseases. It is currently used and sold as an ornamental plant. However, many researchers have conducted studies with the plant in due to its potential biological activity. The interest for this vegetable is in its broad aspect of biological activity, as it has evidenced antibacterial, antipyretic, antiviral, anticancer, antioxidant and other activities. Thuja is a complex plant, because it presents flavonoids, catechins, terpenes, lignans, steroids and polysaccharides in its composition. Phenoic compounds, such as flavonoids, have shown ability to scavenging free radicals and may be used to treat diseases caused by reactive oxygen species. The objective of this study was to determine the hydro alcoholic extract of Thuja occidentalis, using phytochemical assays, antioxidant activity, chemical assays and UPLC-DAD method for the identification and quantification of flavonoids in Thuja occidentalis hydro alcoholic extract. In this study, we also analysed the phytochemical composition (phytochemical screening), the antioxidant activity (DPPH and FRAP), quantified the total phenols (Folin-Ciocalteau), total flavonoids (Aluminium Chloride) and identification and quantification of flavonoids through UPLC-DAD. The validation of the UPLC-DAD method was performed according to the parameters established by ANVISA and ICH, such as linearity, precision, accuracy, recovery, robustness, selectivity, detection limit, quantification limit and system suitability. The results evidenced the presence of flavones, flavononols, flavonols, xanthones, catechins and steroids. In addition, Thuja occidentalis has 2.85% of total phenols and 0.95% of flavonols in its composition. Maximum antioxidant activity of 95.125% with a concentration of 200 μg/mL of hydro alcoholic extract and IC50 of 5.647 μg/mL by the DPPH method and 5,269 mM of Thuja occidentalis extract is required to reduce 50% of the FRAP reagent. The chromatographic method allowed to identify flavonoids present in the sample, among them: myricitrin quercitrin, amentoflavone e Catechin, indicating that the UPLC-DAD is more accurate and reliable than conventional methods for the quantification of flavonoids in Thuja. The UPLC-DAD method was validated, following the ANVISA and ICH parameters and proved to be selective, sensitive, linear, accurate and accurate for the analysis of the extract of Thuja occidentalis and related flavonoids. This method can be applied to the quality control of Thuja occidentalis extract and pharmaceuticals formulations, using flavonoids as markers, since it may be responsible for the therapeutic properties of this plant